NKT Cells in Sepsis - Briana Leung; Hobart W. Harris (Clinical and Developmental Immunology)
Sepsis is currently a leading cause of death in hospital intensive care units. Previous studies suggest that the pathophysiology of sepsis involves the hyperactivation of complex proinflammatory cascades that include the activation of various immune cells and the exuberant secretion of proinflammatory cytokines by these cells. Natural killer T-cells (NKTs) are a sublineage of T cells that share characteristics of conventional T cells and NK cells and bridge innate and adaptive immunity. More recently, NKT cells have been implicated in microbial immunity, including the onset of sepsis. Moreover, apolipoprotein E (apoE), a component of triglyceride-rich lipoproteins, has been shown to be protective in endotoxemia and gram-negative infections in addition to its well-known role in lipid metabolism. Here, we will review the role of NKT cells in sepsis and septic shock, the immunoregulatory role of apoE in the host immune response to infection, and propose a mechanism for this immunoregulation.